Gerakan Bersih Pantai: Kolaborasi Mahasiswa dan Masyarakat dalam Menjaga Kebersihan dan Kelestarian Ekosistem Pesisir di Pantai Panrita Lopi - Muhamad Amir Ariandi; Rizky Zakariyya Rasyad; Renni Mayasari; Muhammad Nur Madani; Yunita Yunita (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2026)
This community service activity aims to enhance public awareness of the importance of maintaining coastal environmental cleanliness through a beach clean-up movement at Panrita Lopi Beach, Muara Badak District. This activity was motivated by the presence of waste scattered along the coastal area, which negatively affects environmental quality, visitor comfort, and the sustainability of the coastal ecosystem. The method applied was a participatory action approach, involving students and local communities directly in environmental education and beach clean-up activities. Data were collected through observation, documentation, and simple interviews to assess initial conditions, implementation processes, and changes after the activity. The results indicate that the beach clean-up movement significantly improved coastal cleanliness, increased community participation, and fostered collective awareness in maintaining environmental sustainability. Furthermore, the improved beach condition contributed positively to visitor comfort and enhanced the potential attractiveness of the area as a local tourism destination. This activity demonstrates that collaboration between students and the community can serve as an effective strategy for preserving coastal ecosystems while supporting the development of sustainable, environmentally based tourism.